Boron nitride membrane and method of making the same
Patent Information
- Application Number
- CN202511486574.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-10-17
AI Technical Summary
[0014]本发明的附加方面和优点将在下面的描述中部分给出,部分将从下面的描述中变得明显,或通过本发明的实践了解到。
Smart Images

Figure CN121307423B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery materials technology, specifically to boron nitride separators and their preparation methods. Background Technology
[0002] With the rapid global proliferation and deepening application of mobile communications and portable electronic devices, the market has placed higher performance demands on rechargeable batteries. This has made lithium-ion battery technology a key direction in the current energy storage field, attracting continuous and widespread research attention. The separator, as one of the key components within a lithium-ion battery, plays a crucial role in isolating the positive and negative electrodes while allowing lithium ions to pass back and forth between them. Current separator materials face some technical bottlenecks, such as relatively poor heat resistance. Therefore, developing a battery separator with excellent heat resistance is one of the current challenges.
[0003] Application content This application aims to at least partially address one of the technical problems in the related art. To this end, one objective of this application is to provide a boron nitride membrane and a method for preparing the same, wherein the boron nitride membrane exhibits excellent heat resistance.
[0004] A first aspect of this application provides a boron nitride membrane, comprising: Base film; A functional layer is disposed on at least one side of the base membrane, the functional layer comprising boron nitride and an adhesive comprising polyethersulfone. This boron nitride membrane exhibits excellent heat resistance, with a heat resistance up to approximately 200°C compared to conventional alumina-coated membranes. Specifically, PES has a high glass transition temperature (approximately 220°C) and melting point (approximately 310°C). Therefore, under relatively high temperature conditions, PES itself will not easily soften, melt, or undergo significant physicochemical changes, maintaining a stable solid structure. This helps provide a relatively stable framework for the boron nitride separator, thereby improving the overall heat resistance of the separator and enabling it to maintain its basic shape and function even at high temperatures. On the other hand, due to the high thermal conductivity of boron nitride, it can quickly conduct heat. When PES is combined with boron nitride, PES can fill the gaps between boron nitride layers and between boron nitride and the base film, enhancing the bonding force between boron nitride layers and between boron nitride and the base film, forming a more compact and stable composite structure. This allows heat to be conducted and diffused more efficiently through the layered structure of boron nitride. As a result, heat will not accumulate excessively in the separator under high temperature conditions, thus improving the stability and heat resistance of the separator under high temperature conditions.
[0005] In some embodiments, at least one of the following conditions is met: The base film includes at least one of polyethylene film and polypropylene film; The thickness of the base film is 12μm to 25μm; The porosity of the base film is 41% to 55%. This is beneficial for improving the battery's charge and discharge efficiency, cycle performance, and energy density.
[0006] In some embodiments, at least one of the following conditions is met: The thickness of the functional layer is 5μm ~ 10μm; The mass ratio of boron nitride to binder in the functional layer is 25~35:2~10. This is beneficial for improving the battery's charge / discharge efficiency, cycle performance, and energy density.
[0007] A second aspect of this application discloses a method for preparing a boron nitride membrane, comprising: Boron nitride ceramic powder, binder, and organic solvent are mixed to obtain a slurry; The slurry is coated on at least one side of the base film to obtain a base film with a slurry coating; The boron nitride membrane is obtained by curing the slurry coating. This method is simple and efficient, suitable for large-scale production, and the boron nitride membrane prepared has excellent performance.
[0008] In some embodiments, the mixing of boron nitride ceramic powder, binder, and organic solvent is performed using a high-efficiency resonant mixer. This helps to obtain a uniformly dispersed slurry.
[0009] In some embodiments, at least one of the following conditions is met: The mixing time is 10 min to 20 min; The vibration frequency of the mixture is 50Hz~100Hz; The vibration intensity of the mixture is 30%~70%; The mass ratio of the boron nitride ceramic powder, the binder, and the organic solvent is 25~35:2~10:25~40; The organic solvent includes at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. This facilitates the preparation of boron nitride membranes with excellent performance and stable structure.
[0010] In some embodiments, the thickness of the slurry coating is 10 μm to 15 μm. This facilitates efficient heat conduction and also helps to increase the migration rate of ions.
[0011] In some embodiments, curing the slurry coating includes: Alcohol is sprayed onto the surface of the slurry coating, and then allowed to air dry. This significantly shortens the curing time, improves production efficiency, accelerates the preparation process of the boron nitride diaphragm, and meets the needs of large-scale production.
[0012] In some embodiments, the concentration of ethanol in the alcohol is ≥99.5%. This helps to further improve the efficiency of curing.
[0013] In some embodiments, at least one of the following conditions is met: The boron nitride ceramic powder has a particle size of 200 nm to 400 nm. The boron nitride ceramic powder is hexagonal boron nitride powder. This helps to further improve the performance of the diaphragm.
[0014] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0015] Figure 1 This is a schematic diagram of the structure of the boron nitride membrane prepared in Example 1 of this application.
[0016] Figure 2 This is a schematic diagram of the structure of the boron nitride membrane prepared in Example 2 of this application.
[0017] Figure 3 This is a TEM image of boron nitride ceramic powder in one embodiment of this application.
[0018] Figure 4 This is a SEM image of the surface of the functional layer in the boron nitride membrane prepared in Example 1 of this application. Detailed Implementation
[0019] The embodiments of this application are described in detail below. The embodiments described below are exemplary and intended to explain this application, and should not be construed as limiting this application.
[0020] This application is based on the inventor's following discoveries and understandings: Currently, traditional lithium-ion battery separators widely employ polyethylene microporous membranes, polypropylene microporous membranes, and three-layer microporous composite membranes composed of polypropylene, polyethylene, and polypropylene. These membranes possess advantages such as excellent mechanical strength, fire resistance, resistance to chemical reagents, good acid and alkali corrosion resistance, good biocompatibility, and non-toxicity. However, these membranes have poor heat resistance; at high temperatures, thermal shrinkage can cause contact between the positive and negative electrodes, leading to rapid localized heat release and posing a significant safety hazard. Adding nano-boron nitride to the aforementioned polyolefin composite membranes can, to some extent, mitigate these problems. Specifically, the boron nitride powder has a layered structure and is coated onto the polyolefin composite membrane. The thin layer helps reduce the membrane thickness, thereby reducing the internal resistance of the lithium-ion battery and optimizing its high-rate discharge and cycle performance. Furthermore, the large gaps between the boron nitride layers and between the boron nitride and the separator facilitate electrolyte flow and lithium-ion insertion and extraction, thus improving the charge / discharge efficiency and capacity of the lithium-ion battery.
[0021] In related technologies, although boron nitride separators can improve the conductivity, heat resistance and liquid absorption / retention capacity of separators to a certain extent, boron nitride separators are still prone to melting at high temperatures, which can lead to battery short circuits and pose serious safety problems. Therefore, the inventors considered developing a boron nitride separator with excellent heat resistance.
[0022] The first aspect of this application proposes a boron nitride diaphragm, with reference to... Figure 1 The system includes a base film 1 and a functional layer 2, wherein the functional layer 2 is disposed on at least one side of the base film 1. Exemplarily, the functional layer can be disposed on one or both sides of the base film. When the functional layer is disposed on both sides of the base film, reference can be made to... Figure 2 The functional layer comprises boron nitride and a binder, wherein the binder comprises polyethersulfone (PES). This boron nitride membrane exhibits not only excellent electrical conductivity but also excellent heat resistance. Specifically, PES has a high glass transition temperature (approximately 220°C) and melting point (approximately 310°C). Therefore, under relatively high temperature conditions, PES itself will not easily soften, melt, or undergo significant physicochemical changes, maintaining a stable solid structure. This helps provide a relatively stable framework for the boron nitride separator, thereby improving the overall heat resistance of the separator and enabling it to maintain its basic shape and function even at high temperatures. On the other hand, due to the high thermal conductivity of boron nitride, it can quickly conduct heat. When PES is combined with boron nitride, PES can fill the gaps between boron nitride layers and between boron nitride and the base film, enhancing the bonding force between boron nitride layers and between boron nitride and the base film, forming a more compact and stable composite structure. This allows heat to be conducted and diffused more efficiently through the layered structure of boron nitride. As a result, heat will not accumulate excessively in the separator under high temperature conditions, thus improving the stability and heat resistance of the separator under high temperature conditions.
[0023] In some embodiments, the base membrane includes a polyolefin membrane, which, for example, can be any one of a polyethylene membrane, a polypropylene membrane, or a mixed membrane composed of polyethylene and polypropylene. The aforementioned polyolefin membrane has excellent chemical stability and is not prone to chemical reactions in the strong redox environment inside the battery or in the electrolyte, thus maintaining long-term stability and ensuring that the battery separator functions normally in the battery. At the same time, the aforementioned base membrane has a certain strength and flexibility, which helps to withstand mechanical stresses such as the compression of electrode materials and changes in electrode volume caused by lithium ion insertion / extraction during battery assembly and charging / discharging, making it less prone to damage, thereby maintaining effective isolation between the positive and negative electrodes inside the battery and preventing short circuits. Furthermore, the aforementioned base membrane has suitable pore size and porosity. Suitable pore size helps lithium ions to pass through smoothly, enabling normal charging and discharging of the battery, while suitable porosity ensures sufficient wetting and storage of the electrolyte, providing channels for lithium ion migration, which is beneficial to improving the charging / discharging efficiency and cycle performance of the battery.
[0024] In some embodiments, the thickness of the base film is 12μm to 25μm, specifically, it can be 12μm, 15μm, 17μm, 20μm, 22μm, 25μm, etc. The thickness of the base film within the above range can reduce the path length of ions migrating inside the battery to a certain extent, thereby reducing the internal resistance of the battery. In addition, with the overall volume of the battery remaining unchanged, the thickness of the base film within the above range can accommodate more electrode active materials, thereby increasing the battery's energy storage capacity and improving the battery's energy density.
[0025] In some embodiments, the porosity of the base film is 41% to 55%, specifically, it can be 41%, 43%, 45%, 47%, 50%, 52%, 55%, etc. The porosity of the base film within the above range helps to reduce the path in the ion migration process, directly reduce the internal resistance of ion transport in the battery, and thus improve the charge and discharge efficiency and rate performance of the battery.
[0026] In some embodiments, the thickness of the functional layer is 5 μm to 10 μm, specifically, it can be 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc. A thickness within this range generally ensures efficient heat conduction and helps improve ion migration rate. This largely avoids the problems that may arise from an excessively thin functional layer, such as insufficient boron nitride and PES content, which would prevent the formation of a stable porous network structure and thus affect the membrane's heat dissipation performance and ion migration rate. It also avoids the problems that may arise from an excessively thick functional layer, such as uneven heat conduction and longer ion migration paths.
[0027] In some embodiments, the mass ratio of boron nitride to binder in the functional layer is 25-35:2-10, specifically, it can be 25:2, 25:7, 25:5, 30:2, 30:5, 30:10, 35:10, etc. A mass ratio of boron nitride to binder within the above range can generally ensure the structural stability of the boron nitride membrane and its excellent conductivity and heat resistance. This largely avoids problems such as decreased structural stability and reduced heat resistance of the membrane due to excessive boron nitride content, and the impact on the conductivity of the membrane due to excessive binder content.
[0028] In a second aspect of this application, a method for preparing a boron nitride membrane is provided, comprising: S10: Boron nitride ceramic powder, binder and organic solvent are mixed to obtain a slurry.
[0029] In this step, the boron nitride ceramic powder, the binder, and the organic solvent are mixed in a high-efficiency resonant mixer, which helps to complete the mixing process efficiently and ensures that the slurry is mixed uniformly. For example, after adding the boron nitride ceramic powder, the binder, and the organic solvent to the high-efficiency resonant mixer, five alumina grinding balls are added for further mixing.
[0030] In some embodiments, the mixing time is 10 to 20 minutes, specifically 10 minutes, 15 minutes, 20 minutes, etc. This mixing time can basically ensure the uniformity of the slurry. It can basically avoid the time waste that may be caused by excessive mixing time, and the unevenness of the slurry that may be caused by excessive mixing time.
[0031] In some embodiments, the mixing frequency is 50Hz to 100Hz, specifically, it can be 50Hz, 60Hz, 70Hz, 80Hz, 90Hz, 100Hz, etc. The mixing frequency within the above range helps to further ensure the uniformity of the slurry.
[0032] In some embodiments, the vibration intensity of the mixture is 30% to 70%, specifically, it can be 30%, 40%, 50%, 60%, 70%, etc. Vibration intensity within the above range helps to further improve the uniformity of the slurry, thereby helping to obtain a structurally stable and uniform diaphragm through subsequent steps.
[0033] In some embodiments, the mass ratio of the boron nitride ceramic powder, the binder, and the organic solvent is 25~35:2~10:25~40. Specifically, the mass ratio of the boron nitride ceramic powder, the binder, and the organic solvent can be 25:2:25, 25:5:25, 25:10:25, 25:10:40, 30:5:35, 30:10:40, 30:10:35, 35:10:40, etc. The above mass ratio can basically ensure that the boron nitride ceramic powder and the binder are completely dissolved in the organic solvent, so that the ratio of boron nitride to binder in the obtained slurry is appropriate, thereby helping to obtain a high-performance boron nitride membrane through subsequent coating and curing operations.
[0034] In some embodiments, the organic solvent includes one or more of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide. These organic solvents can effectively disperse boron nitride ceramic powder, preventing its agglomeration and facilitating the formation of a uniform functional layer in subsequent coating processes. Simultaneously, these organic solvents can fully dissolve PES, forming a uniform solution system. After coating onto the base film, PES can be more evenly distributed and fully bonded with the boron nitride ceramic powder, enhancing the cohesion of the functional layer and its adhesion to the base film, thus ensuring the stability of the membrane structure.
[0035] In some embodiments, the particle size of the boron nitride ceramic powder is 200 nm to 400 nm, specifically 200 nm, 250 nm, 300 nm, 350 nm, and 400 nm. A particle size within this range helps to obtain a uniformly dispersed slurry, ensuring the structural stability of the functional layer. Simultaneously, a suitable particle size facilitates sufficient contact between the boron nitride ceramic powder, PES, and the base membrane, thereby improving the overall performance of the separator. This largely avoids problems such as slurry agglomeration caused by excessively small particle sizes, and weak bonding between the boron nitride ceramic powder and PES caused by excessively large particle sizes.
[0036] In some embodiments, the boron nitride ceramic powder is hexagonal boron nitride powder. Hexagonal boron nitride powder has a graphite-like layered structure, thereby exhibiting excellent high-temperature resistance, excellent thermal conductivity, and excellent machinability, which helps to obtain a high-performance battery separator. Specifically, the surface morphology of the boron nitride ceramic powder is described with reference to... Figure 3 .
[0037] S20: The slurry is coated on at least one side of the base film to obtain a base film with a slurry coating.
[0038] In this step, for example, the slurry obtained above is uniformly coated onto at least one surface of the base film using a coating method, such that the thickness of the slurry coating is 10-15 μm, resulting in a base film with a slurry coating. Specifically, the thickness of the slurry coating can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc. A thickness within the above range can basically ensure that the thickness of the functional layer is within the target range, thereby contributing to efficient heat conduction and improving the ion migration rate.
[0039] S30: Curing the slurry coating to obtain the boron nitride membrane.
[0040] In this step, alcohol is sprayed onto the surface of the slurry coating in the aforementioned base film with a slurry coating, and the slurry coating is cured by natural air drying to obtain a boron nitride membrane. For example, alcohol is miscible with N-methylpyrrolidone, but PES is insoluble in alcohol. When alcohol is sprayed onto the slurry coating containing N-methylpyrrolidone and PES, the alcohol rapidly diffuses and mixes with N-methylpyrrolidone, changing the composition and properties of the coating system. With the addition of alcohol, the solubility of N-methylpyrrolidone in PES gradually decreases. After reaching a certain level, PES precipitates in solid form. As the alcohol evaporates, the solvent in the system continuously decreases, and the PES gradually connect to form a continuous solid network structure, achieving curing and ultimately obtaining a stable boron nitride membrane structure. Using the above-mentioned phase transformation curing method, there is no need for complex heating and cooling processes. After spraying alcohol, it evaporates rapidly at room temperature, and the PES cures quickly. Compared to some methods that require heating to a high temperature and maintaining it for a certain time to cure, this method greatly shortens the curing time, improves production efficiency, accelerates the preparation process of boron nitride membranes, and can meet the needs of large-scale production.
[0041] In some embodiments, ethanol is sprayed evenly onto the surface of the slurry coating using a spray bottle, and can be sprayed 1 to 3 times. This helps to fully wet the surface of the slurry coating with alcohol, thereby increasing the curing rate of the slurry coating.
[0042] In some embodiments, the concentration of ethanol in the alcohol is ≥99.5%. Specifically, the concentration of ethanol in the alcohol can be 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, etc. A concentration within the above range helps the alcohol to quickly diffuse on the surface of the slurry coating after being sprayed onto the coating surface, mix with N-methylpyrrolidone, rapidly change the solubility of PES in the slurry coating system, and cause N-methylpyrrolidone to precipitate rapidly, further accelerating the curing process.
[0043] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.
[0044] Example 1 The boron nitride membrane is prepared using the method described in this application, as follows: Preparation of slurry: 25 kg of boron nitride powder, 5 kg of PES, and 35 kg of N-methylpyrrolidone were placed in a high-efficiency resonant mixer, and 5 alumina grinding balls were added. The mixture was resonantly mixed for 20 min to obtain the slurry.
[0045] Coating and curing: The slurry is coated on one surface of the polyolefin membrane, with a slurry coating thickness of 5 μm. The slurry coating surface is sprayed with alcohol three times and allowed to air dry naturally to obtain a membrane sample with a single functional layer.
[0046] Examples 2-6 Same as Example 1, the main differences are shown in Table 1.
[0047] Comparative Example 1 Same as Example 1, the main differences are shown in Table 1.
[0048] Detection methods The boron nitride diaphragm is placed in a sintering furnace and kept at a specific temperature (e.g., 100℃, 150℃, 200℃, etc.) for 0.5h to 1h. After it has completely cooled down, it is taken out and the curling of the diaphragm is observed. The heat resistance of the diaphragm is judged by the degree of curling.
[0049] Test results The surface of the functional layer in the boron nitride membrane obtained in Example 1 was observed using SEM, see... Figure 4 It can be seen that the surface of the functional layer contains a large number of nanopores and the pore size of the nanopores is relatively uniform, indicating that the structure of the prepared boron nitride membrane is relatively stable.
[0050] Table 1
[0051] Conclusion: The boron nitride membrane prepared in this application has excellent high-temperature resistance.
[0052] In the description of this application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0053] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0054] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A method for preparing a boron nitride diaphragm, characterized in that, include: Boron nitride ceramic powder, binder, and organic solvent are mixed to obtain a slurry; The slurry is coated on at least one side of the base film to obtain a base film with a slurry coating; The slurry coating is cured to obtain the boron nitride membrane. The mixing of boron nitride ceramic powder, binder, and organic solvent is carried out using a high-efficiency resonant mixer. The mixing time is 10-20 minutes, the mixing frequency is 50-100 Hz, and the vibration intensity is 30%-70%. The mass ratio of the boron nitride ceramic powder, the binder, and the organic solvent is 25~35:2~10:25~40; Curing the slurry coating includes: spraying alcohol onto the surface of the slurry coating and allowing it to air dry naturally, wherein the concentration of ethanol in the alcohol is ≥99.5%; The boron nitride membrane comprises: Base film; A functional layer is disposed on at least one side of the base film. The functional layer includes boron nitride and an adhesive, wherein the adhesive includes polyethersulfone, and the mass ratio of boron nitride to adhesive in the functional layer is 25~35:2~10.
2. The preparation method according to claim 1, characterized in that, The boron nitride membrane satisfies at least one of the following conditions: The base film includes at least one of polyethylene film and polypropylene film; The thickness of the base film is 12μm to 25μm; The porosity of the base membrane is 41%~55%.
3. The preparation method according to claim 1, characterized in that, The thickness of the functional layer is 5μm to 10μm.
4. The preparation method according to claim 1, characterized in that, The thickness of the slurry coating is 10μm to 15μm.
5. The preparation method according to claim 1, characterized in that, The organic solvent includes at least one of N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.
6. The preparation method according to claim 1, characterized in that, At least one of the following conditions must be met: The boron nitride ceramic powder has a particle size of 200 nm to 400 nm. The boron nitride ceramic powder is hexagonal boron nitride powder.
Citation Information
Patent Citations
Method of manufacturing the microporous polyolefin composite film with a thermally stable layer at high temperature
CN102017233A
Diaphragm provided with active nano boron nitride coating, and preparation method of diaphragm
CN104600231A
Separator for non-aqueous secondary battery and non-aqueous secondary battery
CN111512471A